Analysis of The Implementation of Countermeasure Policies Against Stunting - Ardilla, Arista; Zulkarnaini, Zulkarnaini; Utaminingsih, Eka; Irafadillah Effendi, Desy; Vita Sari, Dian; Fatmawati, Fatmawati (Babali Publisher, 2024)
Introduction: Stunting is a major nutrition problem worldwide, especially in poor and developing countries. This problem leads to children's suboptimal brain, mental, and cognitive development. The stunting rate globally was 32.6% in 2000, and by 2017, around 150.8 million people were suffering from malnutrition and stunting. This research aims to determine the implementation of stunting prevention policies in the Puskesmas (Public Health Centre) Blang Cut working area.Methods: The research used a qualitative method with a descriptive approach to analyze the implementation of countermeasure policies to reduce stunting. The Health Belief Model was used as the theoretical framework. The methodological orientation of this research was discourse analysis. The study used an interview guide and a voice recorder to collect information from 9 informants.Results: Puskesmas Blang Cut has implemented several countermeasure policies to reduce stunting. These include increasing awareness about the importance of proper nutrition and hygiene, training healthcare workers on stunting prevention, and monitoring children's growth regularly. Implementing these policies has led to a significant reduction in the prevalence of stunting. However, some challenges still need to be addressed, such as increasing access to healthcare services and improving the quality of healthcare facilities.Conclusion: Communication factors related to implementing Countermeasure Policies in Stunting Reduction have been running well. The puskesmas has carried out all stunting reduction program activities, but the more dominant one is the Supplementary Feeding Program for those affected by stunting.